2016
DOI: 10.1161/hypertensionaha.115.06161
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Galectin-3 Pathway Prevents Isoproterenol-Induced Left Ventricular Dysfunction and Fibrosis in Mice

Abstract: Abstract-Galectin-3 (Gal-3) is involved in inflammation, fibrogenesis, and cardiac remodeling. Previous evidence shows that Gal-3 interacts with aldosterone in promoting macrophage infiltration and vascular fibrosis and that Gal-3 genetic and pharmacological inhibition prevents remodeling in a pressure-overload animal model of heart failure. We aimed to explore the contribution of Gal-3 and aldosterone in mechanisms leading to heart failure in a murine model. Male mice with cardiac-specific hyperaldosteronism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(61 citation statements)
references
References 34 publications
1
58
1
1
Order By: Relevance
“…Many clinical association studies have shown that plasma levels of Gal-3 are associated with cardiac function and LV-filling pressures [45,46]. Moreover, studies in animal models of HF revealed that Gal-3 was involved in cardiac remodeling, and both genetic disruption and pharmacological inhibition of Gal-3 resulted in reduced cardiac remodeling, including myocardial fibrosis [43,[47][48][49][50][51][52]. However, because HF is a multi-organ syndrome, other organs could also contribute to increased Gal-3 levels in HF.…”
Section: Fibrosis Marker Gal-3mentioning
confidence: 99%
“…Many clinical association studies have shown that plasma levels of Gal-3 are associated with cardiac function and LV-filling pressures [45,46]. Moreover, studies in animal models of HF revealed that Gal-3 was involved in cardiac remodeling, and both genetic disruption and pharmacological inhibition of Gal-3 resulted in reduced cardiac remodeling, including myocardial fibrosis [43,[47][48][49][50][51][52]. However, because HF is a multi-organ syndrome, other organs could also contribute to increased Gal-3 levels in HF.…”
Section: Fibrosis Marker Gal-3mentioning
confidence: 99%
“…Experimental studies in vitro and in vivo have yielded several lines of evidence for Gal-3 as a mediator of heart disease. First, when tested ex vivo, Gal-3 promoted fibroblast proliferation and expression of fibrogenic genes (Frunza et al, 2016;Ibarrola et al, 2018;Mackinnon et al, 2012;Takemoto et al, 2016;Vergaro et al, 2016;Yu et al, 2013). Gal-3 also promoted the innate immune response by stimulating monocyte migration and expression of inflammatory cytokines and chemokines (Jaquenod De Giusti et al, 2015;Nachtigal et al, 2008;Sharma et al, 2004;Vasta, 2012).…”
Section: In Heart Diseasementioning
confidence: 99%
“…Galactine‐3 is a pleiotropic lectin with an important role in cell proliferation, adhesion, differentiation, angiogenesis, and apoptosis. Galectin‐3 activates many profibrotic factors, promotes fibroblast proliferation and transformation, and mediates collagen production . Higher levels of galectine‐3 have been associated with a worse prognosis in patients with acute respiratory distress syndrome .…”
Section: Discussionmentioning
confidence: 99%